Fabrication of boron doped diamond cantilevers by means of dry ICP etching. (September 2019) - Vojs, M; Marton, M; Jančo, M; Behúl, M; Řeháček, V; Michniak, P; Držík, M; Redhammer, R
Abstract: This paper is focused on the preparation of boron doped diamond (BDD) cantilevers for MEMS applications. Hot filament CVD diamond deposition technique was used for preparation of highly boron doped thin film. The fabrication process consisted only of dry etching steps and masking process, no wet etching of substrate was used. Therefore, it was necessary to optimize both anisotropic and isotropic etching to release the cantilever structure from silicon substrate. Doped diamond cantilevers were etched by reactive ion etching using inductively coupled plasma (ICP RIE) through aluminum etching masks. The optimal properties of fabrication process led to high quality MEMS structures. The resulting cantilevers were investigated by scanning electron microscopy (SEM) and laser vibrometer system. Finally, we demonstrate a BDD cantilever (5 μm width) with the main resonant frequencies at 22.2 kHz, 46.6 kHz, 52.2 kHz and 65.6 kHz.